EFFECTS OF SLOPE ON SOIL LOSS RATE FROM RILL EROSION IN BIU AREA, BORNO STATE, NIGERIA - Madu, I.; Emmanuel, V.I.; Mohammed, T.A.; Ibrahim, Z.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted at six different sites (Piku, Kigir, Dam, Mirnga, Mandaragrau and Gunda) in Biu area, under different soil types, topography and vegetation to estimate the soil loss rates on slope due to rill erosion. The study was carried out on annual bases between March and December in 2020. The annual precipitation varied from 699.00 – 896.00mm. and the rainfall erosivity ranged from 351.00 – 485.00 MJmmha-1hr-1yr-1, respectively across the sites. Soil erodibility (0.70 – 0.80) slope length (435.00 – 785.00m), and slope steepness (6 – 9%) cover management factor (0.12 – 0.23) and protection management (0.12), were used as predictor variables in Revised Universal Soil Loss Equation Version 2 (RUSLE2) 2016, across the sites. Six hectares of overland flow sites consisting of rills were selected at random at each site for the study. About 144 soil samples were collected from six sites and RUSLE2 model annual estimation of soil loss was 260.00 – 447.00, respectively. High soil loss was recorded at Piku site with a respective value of 447.00. Based on the result of this study, management of terraces, mulching, cover crops and vegetation, no – tillage method, buffer zones, contour bonds, check dams, grassed water ways and hillside water ponds are recommended to reduce the length of the slope and consequently the soil and water loss.